Analysis of the Implementation of Holistic-Based Midwifery Care in Primary Level Health Services at Plered Health Center, Purwakarta Regency, Indonesia - Prihantini, Titin (HM Publisher, 2024)
Holistic-based midwifery care is a caring approach that focuses on physical, psychological, social, and spiritual aspects. The aim of this research is to analyze the implementation of holistic-based midwifery care in primary-level health services at the Plered Health Center, Purwakarta Regency, Indonesia. This research uses a descriptive method with a qualitative approach. The research subjects were midwives at the Plered Health Center, Purwakarta Regency. Data was collected through in-depth interviews, observation, and documentation. Data analysis was carried out qualitatively using thematic analysis techniques. The results of the research show that the implementation of holistic-based midwifery care at the Plered Health Center, Purwakarta Regency, has been going quite well. Midwives have implemented midwifery care that focuses on physical, psychological, social, and spiritual aspects. However, there are still several aspects that need to be improved, such as: Increasing the competency of midwives in providing holistic midwifery care; Better collaboration between midwives and other health workers and support from Health Center management.